Outcomes of robot-assisted simple enucleation of renal masses: A single European center experience. Issue 18 (May 2017) - Matei, Deliu Victor; Vartolomei, Mihai Dorin; Musi, Gennaro; Renne, Giuseppe; Tringali, Valeria Maria Lucia; Mistretta, Francesco Alessandro; Delor, Maurizio; Russo, Andrea; Cioffi, Antonio; Bianchi, Roberto; Cozzi, Gabriele; Di Trapani, Ettore; et al.
Abstract : Abstract: The aim of this study was to assess the ability of pre-and intraoperative parameters, to predict the risk of perioperative complications after robot-assisted laparoscopic simple enucleation (RASE) of renal masses, and to evaluate the rate of trifecta achievement of this approach stratifying the cohort according to the use of ischemia during the enucleation. From April 2009 to June 2016, 129 patients underwent RASE at our Institution. We stratified the procedures in 2 groups: clamping and clamp-less RASE. After RASE, all specimens were retrospectively reviewed to assess the surface–intermediate–base (SIB) scoring system. Patients were followed-up according to the European Association of Urology guidelines recommendations. All pre-, intra-, and postoperative outcomes were prospectively collected in a customized database and retrospectively analyzed. A total of 112 (86.8%) patients underwent a pure RASE and 17 (13.2%) had a hybrid according to SIB classification system. The mean age was 61.17 years. In 21 patients (16.3%), complications occurred, 13 (61.9%) were Clavien 1 and 2, while 8 were Clavien 3a and b complications. Statistical significant association with complications was found in patients with American Society of Anestesiology (ASA) score 3 (44.5%, P  = .04), longer mean operative time (OT) 195 versus 161.36 minutes ( P  =.03), mean postoperative hemoglobin (Hb) 10.1 versus 11.8 ( P  <.001), and mean ΔHb 3.59 versus 2.18 ( P  <.001). In multivariate logistic regression, only longer OT and ΔHb were statistical significant predictive factors for complications. In sub-group analysis, clamp-less RASE was safe in terms of complications (14.1%), positive surgical margins (1.3%), and mid-term local recurrence (1.3%). Although in this approach there is higher EBL ( P  = .01), this had no impact on ΔHb ( P  = .28). A clamp-less approach was associated with a higher rate of SIB 0 (71.8% vs 51%, P  = .02), higher trifecta achievement (84.6% vs 62.7%, P  = .004), and better impact on serum creatinine (mean 0.83 vs 0.91, P  = .01). RASE of renal tumors is a safe technique with very good postoperative outcomes. Complication rate is low and associated with ASA score >3, longer OT, and ΔHb. RASE is suitable for the clamp-less approach, which allows to perform easier the pure enucleation (SIB 0) and to obtain higher rates of trifecta outcomes.